Entre o ajeum e a “comida afro-indígena” : Mãe Neide Oyá D’Oxum e a alimentação na Serra da Barriga, Alagoas - Barbosa, Isabela Maria Pereira (2018)
This Master Thesis analyze the feeding in the Serra da Barriga, Alagoas, from the impacts around the creation of Baobá Raízes e Tradições Restaurant, founded by ialorixá and chef Mãe Neide Oyá D’Oxum. Having as methodological resource the analysis of the ialorixá’s trajectory, the discourses around the food maked in her restaurant and her role as “guardian of memory”, the work problematizes the constructions and the tensions between the interfaces about “quilombola´s food”, “sagrado´s food”, and the “afro-indigena food” in that location. Therefore, evidence this debates from an ethnographic search that had as itinerary the ialorixá’s narratives and reforced by “eco-technical tourism” in Baobá Raízes e Tradições Restaurant, located in Serra da Barriga, siding by the Parque Memorial Quilombo dos Palmares (PMQP), and silencing of the residents who live around fo PMQP and the Muquém Quilombola Community.